The Role of Paternalistic Leadership in Organizational Virtuousness - Yazin Salim Muhammed; Abbass Ahmed Mohammed; Ihab Zeyad mohammed; Ahmed Abdullah Amanah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The study aimed to investigate the influence of paternalistic leadership on organizational virtuewithin the Dean's educational group. To achieve this goal, the study utilized paternalistic leadership,including ethical, authoritarian, and benevolent leadership, and organisational virtueousness, includingoptimism, trust, empathy, integrity, and forgiveness. Using a questionnaire including (125) workers ofKarbala Cement Company, a random sample of them was chosen for the study area. The correlationcoefficient (Person) was utilized, and the significance of the correlation link between the two variableswas determined using the (t) and (F) tests. The researcher found that paternalistic leadershipsignificantly influences organizational virtuousness, as determined by calculating the percentagecontribution of the independent variable to the dependent variable using (R2). The study suggests thatKarbala Cement Company prioritizes paternalistic leadership as a crucial aspect of its work andorganizational virtue.